Defensive Mechanisms of Mikania micrantha Likely Enhance Its Invasiveness as One of the World’s Worst Alien Species - David R. Clements; Hisashi Kato-Noguchi (Plants)
Mikania micrantha Kunth is native to tropical America and has invaded tropical and subtropical Asia and numerous Pacific Islands. It forms dense thickets and reduces native species diversity and populations in its introduced range. This invasive vine also seriously impacts many agricultural crops and is listed as one of the world’s 100 worst invasive alien species. Its life history characteristics, such as the production of large numbers of wind-dispersed seeds, vegetative reproduction, rapid growth, and genetic diversity all contribute to its invasiveness. In this review, we focus on how mechanisms to defend against its natural enemies boost the invasiveness of M. micrantha. It possesses potent defenses against natural enemies such as pathogenic fungi, herbivorous insects, and parasitic nematodes, and exhibits allelopathic potential against plant competitors. These defensive abilities, in concert with its formidable life history characteristics, contribute to the invasiveness of M. micrantha, potentially leading to further naturalization. Several other reviews have summarized the biology and management of the species, but ours is the first review to focus on how the defensive mechanisms of M. micrantha likely enhance its invasiveness. Relatively little is known about the array of defensive capabilities of M. micrantha; therefore, there is considerable scope for further research on its chemical defenses.